Using slaughter weight to predict weight and yield of primal cuts of carcass from buffaloes - Jorge, André Mendes [UNESP]; Pinheiro, Rafael Silvio Bonilha [UNESP]; Francisco, Caroline de Lima [UNESP]; Castilhos, André Michel de [UNESP]; Puoli Filho, José Nicolau Próspero [UNESP]; Brandão da Silva, Maurícia [UNESP]; Rivaroli, Dayane Cristina [UNESP]; Coutinho, Carolina Cesarino [UNESP]; Cominotte, Alexandre [UNESP]; Padovan, Isabela de Mello [UNESP] (My University, 2013)
The knowledge of the meat production from different buffalo breeds and their crossings in different feeding systems becomes necessary for the supply of subsidies to whole productive meat chain. Some quantitative carcass traits of Mediterranean buffaloes bulls, finished in feedlot, with initial age of fourteen months and 330 kg live weight, slaughtered with 450, 480, 510 and 540 kg, were evaluated. The diet contained 13% crude protein, 2.68 Mcal digestible energy/kg DM and a roughage: concentrate ratio of 25:75. Regression equations for prediction weight and yield of primal cuts of carcass as a function of slaughter weight were obtained. Carcass dressing percent increased as the slaughter weight increased (49.2; 49.5; 49.7; and 49.9%). The Pistola Style cut weight although increasing linearly in weight (108.2; 117.6; 124.0 and 130.7 kg) as the slaughter weight increased, declined linearly when expressed in relation to cold carcass weight (49.5; 49.0; 48.6 and 48.2%). In this experimental conditions Mediterranean young bulls slaughtered between 450 to 540 kg of live weight showed increasing yields of cold carcass, forequarter and thin flank.
Keywords: Carcass dressing; Cold carcass; Forequarter; Pistol style cut; Thin flank